2011
DOI: 10.1002/cssc.201000405
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopentyl Methyl Ether: An Alternative Solvent for Palladium‐Catalyzed Direct Arylation of Heteroaromatics

Abstract: Some ethers, such as cyclopentyl methyl ether and di-n-butyl ether, which can be considered as "greener" solvents than N,N-dimethylacetamide (DMAc) or DMF, can be advantageously employed for the palladium-catalyzed direct arylation of heteroaromatics. In the presence of such ethers and only 0.5-1 mol % of palladium catalysts at 125-150 °C, the direct 5-arylation of thiazoles, thiophenes, or furans by using aryl bromides as coupling partners proceeds in moderate to high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 78 publications
0
30
0
Order By: Relevance
“…CPME is a solvent with higher thermochemical stability in comparison with other ethereal solvents [43], and, in preliminary tests, it was evaluated under similar experimental conditions in FUR hydrogenation, and it was ruled out its participation in the catalytic process. On the other hand, bentonite and sepiolite supports were also evaluated in the FUR hydrogenation using similar experimental conditions, and, in both cases, FUR conversion was negligible.…”
Section: Catalytic Testsmentioning
confidence: 99%
“…CPME is a solvent with higher thermochemical stability in comparison with other ethereal solvents [43], and, in preliminary tests, it was evaluated under similar experimental conditions in FUR hydrogenation, and it was ruled out its participation in the catalytic process. On the other hand, bentonite and sepiolite supports were also evaluated in the FUR hydrogenation using similar experimental conditions, and, in both cases, FUR conversion was negligible.…”
Section: Catalytic Testsmentioning
confidence: 99%
“…The catalytic system Pd(OAc) 2 associated to PCy 3 in the presence of KOAc in CMPE 14,15 allows 55 the regioselective C5 functionalization of 2-ethyl-4-methylthiazole giving rise to the formation in one step of compound 1 in 46% yield. The use of 3-methylbenzothiophene led to the formation of 2 in a similar yield of 40%.…”
mentioning
confidence: 99%
“…[42] On this subject it is worth noting that in a recent discussion of the parameters that govern the activation barriers of the C À H bond in heteroarenes, Gorelsky included furan in a class (Class II) for which heteroarene-catalyst electronic interaction energies define the most reactive C À H bonds and he reported that in arylation of furan Ca À H bonds are more reactive than Cb À H bonds in the CMD process due to more negative interaction energy at the Ca site. [45] We believe it is also useful to point out that, although intermolecular direct C-2 or C-5 arylation reaction of furans are strongly favoured, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]41,42,46] successful intermolecular Pd-catalyzed C-4 arylations of furan substrates have been described. Thus, in 2009, Zhu and co-workers found that 2,5-diaryl-3-fluorofurans 65 underwent C-4 arylation with a variety of aryl bromides in NMP at 110-120 8C in the presence of KOAc as the base and a catalytic amount of PdCl 2 A C H T U N G T R E N N U N G (PPh 3 ) 2 (Scheme 28).…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 99%
“…It should also be noted that in all these reactions only traces of in situ decarboxylation products were observed. [29] Again in 2012, Doucet and co-workers examined the direct arylation of five-membered heteroarenes with one heteroatom bearing a 1,1-dicyanovinyl group at C-2 and found that these electron-poor substrates underwent C-5 arylation on treatment with aryl bromides bearing an electron-withdrawing group in cyclopentyl methyl ether (CPME), [30,34] a solvent greener than DMA and DMF, at 125 8C in the presence of KOAc as the base and a catalytic quantity of PdCl-…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 99%
See 1 more Smart Citation